DELL’AZZURRO SILENZIO - Parra Cancino, Juan; MusikFabrik concert at Zentrifuge, Bonn Zentrifuge, Bonn, DE 12 September 2024 (2024)
Live Electronics
Performances with MusikFabrik. September 12, 2024, 20hrs Zentrifuge Bonn, DEMusic by Luigi Nono
FRIS
Editorial review
Keywords: Music, Thought and Technology